Dialekt-Standard-Variation im ungesteuerten Zweitspracherwerb des Deutschen Eine soziolinguistische Analyse zum Erwerb von Variation bei erwachsenen Lernenden - Ender, Andrea (DaZ-Forschung [DaZ-For], 2022)
The coexistence of dialect and standard in the German-speaking part of Switzerland offers very interesting framework conditions for investigating the acquisition of linguistic variation in a second language context in more detail. Against this background, the present study focuses on the social significance of languages and varieties and their influence on the construction of the linguistic repertoire in adult learners with different first languages and with variable personal and social framework conditions of language acquisition. It investigates how second language users deal with the existing dialect-standard variation in input, to what extent they integrate the two codes into their second language knowledge and what attitudes towards dialect and standard they develop from the specific acquisition situation. Overall, the work provides information on German acquisition in the study area of Switzerland, but is more generally related to questions on the socio-indexicality of language and language variation in the context of second language acquisition.